"Do they mean what they say?" Measuring greenwash in the sustainable property development sector. Issue 4 (16th August 2021) - Quoquab, Farzana; Sivadasan, Rames; Mohammad, Jihad
Abstract : Purpose: This study aims to measure the greenwash construct in the sustainable property development (GSPD) context. Property development products such as residential homes, which are generally high-priced, require a long-term financial commitment from the consumers. It makes the property development sector unique. Hence, a specific scale is required to measure greenwash activities in this specific context by the marketers. However, the scale available to measure the greenwash construct is general which is not suitable to use in this particular context. The present study is an attempt to fill this gap in the literature. Design/methodology/approach: Three studies were conducted to develop the GSPD measure in different phases. In developing the scale, qualitative interviews (study 1) were conducted to generate the initial pool of items. The preliminary set of questions were then validated (content and face validity) by experts' opinions. Exploratory factor analysis (using SPSS) was conducted to extract the factor structure of the newly developed measure (study 2) which was then again validated to ensure predictive reliability and nomological validity by using the SEM-PLS technique (study 3). Findings: The exploratory factor analysis result revealed that greenwash in sustainable property development (GSPD) is a multi-dimensional construct. The dimensions are namely, false claims and misleading claims. The confirmatory composite analysis confirmed these two dimensions. Practical implications: This newly developed GSPD scale will enable the researchers to measure the greenwash activities practiced by some of the housing developers. Marketers will be conscious to avoid such activities. Moreover, the government agencies may use this scale to monitor measure and deter greenwashing activities by property development companies. Originality/value: This is a pioneer study that develops and validates a new scale to measure greenwash construct in sustainable property development in a developing context i.e. Malaysia. In addition, this study operationalized the greenwash construct in sustainable property development as a multi-dimensional behavioural construct determined by two dimensions i.e. false claims and misleading claims.